2022
DOI: 10.1111/jmwh.13414
|View full text |Cite
|
Sign up to set email alerts
|

Toward Optimal Emotional Care During the Experience of Miscarriage: An Integrative Review of the Perspectives of Women, Partners, and Health Care Providers

Abstract: Introduction Miscarriage is frequently associated with significant emotional impact, causing psychological distress, trauma, and grief. Unfortunately, women and partners frequently report dissatisfaction with care around miscarriage, and health care providers report feeling ill‐prepared and underequipped to provide emotional support. This integrative review synthesizes the individual perspectives of the woman experiencing the miscarriage, the partner, and the different health care provider roles involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 84 publications
0
25
0
Order By: Relevance
“…Findings of qualitative perinatal studies identified similar emotions experienced by women after an unexpected diagnosis of high-risk pregnancy, 43,44 hypertensive disorder, 45,46 preterm labor, 47 and early pregnancy loss. 48 The concept of unmet expectations and broken or shattered expectations identified in this review was also described in studies of unexpected stillbirth, 49 perinatal loss, 50 preterm birth, 51 fetal anomaly, 7,8 and newborn admission to the neonatal intensive care unit. 52 Loss was a major concept, similar to other studies.…”
Section: Discussionmentioning
confidence: 86%
“…Findings of qualitative perinatal studies identified similar emotions experienced by women after an unexpected diagnosis of high-risk pregnancy, 43,44 hypertensive disorder, 45,46 preterm labor, 47 and early pregnancy loss. 48 The concept of unmet expectations and broken or shattered expectations identified in this review was also described in studies of unexpected stillbirth, 49 perinatal loss, 50 preterm birth, 51 fetal anomaly, 7,8 and newborn admission to the neonatal intensive care unit. 52 Loss was a major concept, similar to other studies.…”
Section: Discussionmentioning
confidence: 86%
“…Chavez et al (2019) report that 42% of men describe emotional trauma both during and following pregnancy loss, and McGarva-Collins et al (2022) document intrusive and re-emergent chronic grief reactions in partners who felt the need to act up to male stereotypes in their qualitative study. Providing partners with information, support, and recognising their experiences of loss will contribute to the provision of optimal care (Lee et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to engaging in any activity to assist with the com-pletion of the process of emptying the uterus, the needs and desires of the patient should be considered. 3 Following an initial assessment of the patient to determine that they are hemodynamically stable and not at risk for infection, the approach to next steps needs to include a discussion with the patient to assess their preferences related to their care. These preferences may include a desire for privacy, fear of pain, need for expediency, economic considerations, previous experience with induced abortion or miscarriage management, ability to manage symptoms independently, and risk of complications.…”
Section: Patient-centered Early Pregnancy Loss Carementioning
confidence: 99%
“…Multiple resources are available to help guide the conversation with the patient about what is the best approach to resolve the miscarriage. 3…”
Section: Patient-centered Early Pregnancy Loss Carementioning
confidence: 99%